MENINGKATKAN KUALITAS GENERASI MUDA MELALUI PEMERIKSAAN HAEMOGLOBIN, HEMATOKRIT DAN GULA DARAH SISWA SMA NEGERI I TANJUNG SAKTI - Margareta Haiti; Victoria Ire Tominik; Diana Febriani (Universitas katolik Musi Charitas, 2018)
Hemoglobin is the main protein of the human body that serves as a carrier of oxygen to the tissues and transport media of carbon dioxide from the body tissues of the lungs, the oxygen the body needs as a source of energy that will generate power so that humans are able to execute duties or daily occultation. The main source of haemoglobin is iron which is the source of the nutrient intake we consume. Hemoglobin examination is one of the most frequent blood tests performed by each laboratory because hemoglobin examination in the blood has an important role in the diagnosis of a disease. The usefulness of examining hemoglobin levels is to assess the level of anemia, response to anemia therapy, or disease progression associated with anemia and polycythemia. Hematocyte examination is also important for assessing the normal state or not of erythrocytes and blood volume as well as related to hemoglobin in the body. Decreased hematocrit is one indicator of anemia caused by various factors. Blood glucose is the result of carbihydrate decomposition and glycogen changes in the liver. Glucose examination in darh is a screening procedure that shows the inability of the pancreas to produce insulin, the inability of the small intestine to absorb glucose, the inability of cells to use glucose efficiently or the inability of the liver to collect and solve glycogen. Keywords: Haemoglobin, Hematocrit and Glucose levels in blood